Fungsi Badan Pemberdayaan Masyarakat Desa Dalam Penyelenggaraan Pemerintahan Desa Sepoyu Kabupaten Lamandau Kalimantan Tengah - ARIYA PANJI ANUGRAHNO; Dzunuwanus Ghulam Manar; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2015)
ABSTRACT The implementation of democracy in Indonesia have opted to include the public in the administration. Village Consultative Institution is a part of community participation in the implementation of the village administration, based on Law No. 32 of 2004 that Village Consultative Instiution has a function to set the village rules with the village chief, to accommodate, and share public aspirations. However, Village Consultative Institution of Sepoyu has not been propely functioned. This research aims to discover; (1) the cause of the ineffectiveness of Village Consultative Instiution function as a public representative body at the village administration of Sepoyu the period of office 2010-2014, in accordance with Law No. 32 of 2004, (2) and discover Lamandau District government's role in carrying out the functions of representation of the public in the implementation of the government of Sepoyu village. This research is descriptive research with the qualitative approach. The methods of collecting data in this research use interview and documentation. The data’s analysis uses the descriptive analysis to describe the situation in the research obviously without any manipulation. The study found that the function of Village Consultative Instiution in the rule-making village of Sepoyu were not optimal, which has only produced one rule Village during his tenure due to lack of coordination between the village chief and members of Village Consultative Instiution. Besides, the personal conflicts that occur between the Chairman of the Village Consultative Instiution and Village Chief of Sepoyu also become an obstacle to the performance of The Village Consultative Instiution of Sepoyu in carrying out its functions. Implementation of community representation function by the Village Consultative Instiution Sepoyu in accommodating aspirations of society was also not performing well. This was caused by the lack of communication in the public forum of Sepoyu village whereas the community of Sepoyu can only rely on the Musrenbangdes in regarding to communicate their aspirations. The role of Lamandau government through BPMD of Lamandau District in order to improve the function of government officers village and also include the Village Consultative Instiution has not been implemented well due to lack of budget and regional difficulty accessing. In carrying out the functions, the Village Consultative Instiution needs to optimize the coordination between the village chief and members of Village Consultative Institution, repair relationships between the Village Chief and Chairman of Sepoyu, and also increase the budget of BPMD Lamandau due to the program that aims to improve the function of government officers village